2022
DOI: 10.1007/s00127-022-02306-x
|View full text |Cite
|
Sign up to set email alerts
|

Problem drinking recognition among UK military personnel: prevalence and associations

Abstract: Purpose Despite the higher prevalence of problem drinking in the UK military compared to the general population, problem recognition appears to be low, and little is known about which groups are more likely to recognise a problem. This study examined prevalence of problem drinking recognition and its associations. Methods We analysed data from 6400 regular serving and ex-serving personnel, collected in phase 3 (2014–2016) of the King's Centre for Military … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Routine alcohol screening (Box 3) is recommended across adult medical settings because it is often unrecognized by drinkers 232 and because of how commonly individuals with AUDs interact with the healthcare system. For example, in one study of the U.K. hospital system, one in five patients used alcohol harmfully and one in ten patients had alcohol dependence 233 .…”
Section: Screeningmentioning
confidence: 99%
“…Routine alcohol screening (Box 3) is recommended across adult medical settings because it is often unrecognized by drinkers 232 and because of how commonly individuals with AUDs interact with the healthcare system. For example, in one study of the U.K. hospital system, one in five patients used alcohol harmfully and one in ten patients had alcohol dependence 233 .…”
Section: Screeningmentioning
confidence: 99%
“…Routine alcohol screening (Box 3) is recommended across adult medical settings because it is often unrecognized by drinkers 227 and because of how commonly individuals with an AUD interact with the health-care system. For example, in one study of the UK hospital system, one in five patients used alcohol harmfully and one in ten patients had alcohol dependence 228 .…”
Section: Screeningmentioning
confidence: 99%
“…Lack of problem awareness and recognition is the most frequent reason for not seeking treatment and suggests that routine monitoring in healthcare settings using a Screening, Brief‐Intervention, and Treatment (SBIRT) approach may be useful in raising awareness, catalyzing self‐directed change, and connecting individuals to more intensive treatments (Hargraves et al, 2017; MacKillop et al, 2022; Probst et al, 2015). A recent study investigating the prevalence of problem drinking recognition and its associations reported that greater problem drinking severity, poorer mental or physical health, and negative life experiences facilitated problem drinking recognition (Spanakis et al, 2022). Notably, the literature regarding the efficacy of SBIRT style interventions across alcohol use severity is mixed, with some studies suggesting greater efficacy in individuals with mild AUD vs. severe AUD and some reporting efficacy in individuals with alcohol dependence (Field et al, 2010).…”
Section: Introductionmentioning
confidence: 99%